Efektivitas Media Pembelajaran Kartu Bergambar pada Pemahaman IPS Kelas 8 SMP Baitul Quran Ponjong - Nurullaila Indrianingrum; Sukadari Sukadari (UM Purwokerto Press, 2022)
This study aims to determine the effectiveness of the application of picture card learning media to 8th grade students of Baitul Quran Ponjong Middle School after using picture card learning media on the subject of Change in Colonial Society and the Growth of National Spirit. This research is experimental in nature so that the method used is a quantitative method. The research subjects were 8th grade students of Baitul Quran Ponjong Middle School with a total population of 30 people. The research sample was taken using simple random sampling technique. There was a fairly high increase from the average pretest to posttest scores after being given treatment in the form of picture card learning media, the comparison was 25.7 or an increase of 47.8%.